Hydrogenation of Polyesters to Polyether Polyols - Stadler, Bernhard M.; Hinze, Sandra; Tin, Sergey; Vries, Johannes G. (ChemSusChem, 2019)
The amount of plastic waste is continuously increasing. Besides conventional recycling, one solution to deal with this problem could be to use this waste as a resource for novel materials. In this study, polyesters are hydrogenated to give polyether polyols by using in situ‐generated Ru‐Triphos catalysts in combination with Lewis acids. The choice of Lewis acid and its concentration relative to the ruthenium catalyst are found to determine the selectivity of the reaction. Monitoring of the molecular weight during the reaction confirms a sequential mechanism in which the diols that are formed by hydrogenation are etherified to the polyethers. To probe the applicability of this tandem hydrogenation etherification approach, a range of polyester substrates is investigated. The oligoether products that form in these reactions have the chain lengths that are appropriate for application in the adhesives and coatings industries. This strategy makes polyether polyols accessible that are otherwise difficult to obtain from conventional fossil‐based feedstocks. Don't hydrolyze, convert: It is possible to convert polyesters in a one‐pot process into polyethers by using an in situ‐generated Ru‐Triphos catalyst in combination with a Lewis acid and molecular hydrogen. This reaction opens up a novel field for polyester recycling and makes polyether polyols accessible that are otherwise difficult to obtain from conventional fossil‐based feedstocks.